Determine the printability of PCL for making of tissue scaffold - Teo, Pearlyn Pei Lin (2016)
3D printing is one of the upcoming trends in every industry. It does not just apply to printing spare parts of a machinery, biomedical industry benefited as well. Tissue engineering had been relying on 3D printing technique to fabricate customized organ scaffold with the use of biopolymer. Numeral FDA-approved biopolymers have displayed biocompatibility and yet being able to mimic human properties. To enhance the properties of the scaffolds, nanocomposite used as fillers. In this project, the properties and cell viability of different concentration of multi-walled carbon nanotubes (f-MWCNTs) in 8% polycaprolactone (PCL) with chloroform solvent investigated. Solvent casting of films and printing 0°/90° grid scaffolds were prepared to find out its material properties, physical evaluation, degradation rate, cell viability and cell attachment. Scaffolds designed using BioCAD® software and printed using BioFactory®, a 3D bioprinter. 0°/90° orientation was chosen to print for the scaffold as it has the best resistant to compression and yield stress. With high PCL content that can correlate to high mechanical properties, a maximum of 8% PCL was able to print via BioFactory®. Chloroform, a high dissolution solvent, was used to dissolve PCL. The high tendency for f-MWCNT particles to be bonded by van der Waal bonding which poses a serious challenge when it comes to printing of f-MWCNT with PCL scaffold. Using 1% & 3% f-MWCNT 8% PCL solution, the maximum it can print was 10 layers. Hence, it is not possible to be an ECM. Instead of ECM, it can be thin layer of patches. Cell viability and attachment shown positive in the presence of the f-MWCNT. As f-MWCNT content increases in 8% PCL, the stronger the mechanical properties it become. With higher mechanical properties, shorter the degradation timing is shown. In all these testing, f-MWCNT did enhance PCL scaffolds without compromising biocompatibility and yet improve mechanical properties. Due to the fast aggregation rate of f-MWCNT, the ideal printing setting would be 8%PCL 3%f-MWCNT.